2012
DOI: 10.1128/jvi.07141-11
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Simian Immunodeficiency Virus Transmission in African Green Monkeys: Susceptibility to Infection Is Proportional to Target Cell Availability at Mucosal Sites

Abstract: African green monkeys (AGMs) are naturally infected with a simian immunodeficiency virus (SIVagm) that is nonpathogenic in its host. Although SIVagm is common and widespread, little is known about the mechanisms that govern its transmission. Since the earliest virus-host interactions may provide key insights into the nonpathogenic phenotype of SIVagm, we developed a mucosal transmission model for this virus. Using plasma from an acutely infected AGM as the virus inoculum, we exposed adult and juvenile AGMs, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 80 publications
4
75
1
Order By: Relevance
“…A recent report showed that AGMs are readily infected when mucosally inoculated with SIVagm at high viral titers, and that viral susceptibility correlated with higher levels of CCR5-expressing CD4 ϩ T cells in adult and juvenile AGMs, further supporting the notion that the paucity of CCR5-and CD4-expressing T cells in the infant gastrointestinal tract contributes to the rarity of vertical transmission in this species (55). While the limited availability of target cells likely contributes to the rarity of infant infection, SIV infection of the natural host species, sooty mangabeys, has been initiated in the setting of CCR5-null mutations (56).…”
Section: Discussionmentioning
confidence: 65%
“…A recent report showed that AGMs are readily infected when mucosally inoculated with SIVagm at high viral titers, and that viral susceptibility correlated with higher levels of CCR5-expressing CD4 ϩ T cells in adult and juvenile AGMs, further supporting the notion that the paucity of CCR5-and CD4-expressing T cells in the infant gastrointestinal tract contributes to the rarity of vertical transmission in this species (55). While the limited availability of target cells likely contributes to the rarity of infant infection, SIV infection of the natural host species, sooty mangabeys, has been initiated in the setting of CCR5-null mutations (56).…”
Section: Discussionmentioning
confidence: 65%
“…ϩ T cells at the site of infection (28). Therefore, it is tempting to speculate that viral clearance results from the complete loss of CD4 ϩ T cells, and the data suggest that this loss in AGMs would not lead to immunodeficiency due to the immunological functioning of the CD8␣␣ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma SIVsabBH66 viral RNA loads were quantified by real-time PCR, as described previously (30,31). Whole blood and mononuclear cells isolated from intestinal biopsies were analyzed by flow cytometry, as described previously (9).…”
Section: Methodsmentioning
confidence: 99%